1996
DOI: 10.1042/cs0910567
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Endothelium-Dependent and Independent Dilatation of Forearm Resistance Arteries in Men with Diet-Treated Non-Insulin-Dependent Diabetes: Role of Dyslipidaemia

Abstract: 1. We measured endothelium-dependent and independent dilatation of forearm resistance arteries in 29 men with diet-treated non-insulin-dependent diabetes mellitus and 18 age- and sex-matched control subjects. None of the diabetic patients had hypercholesterolaemia, overt hypertension or microproteinuria. 2. We examined endogenous and exogenous nitric oxide-mediated vasodilatation by measuring forearm blood flow with venous occlusive plethysmography after administration of acetylcholine (7.5 and 15 micrograms/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
116
3
10

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(145 citation statements)
references
References 19 publications
16
116
3
10
Order By: Relevance
“…We recently performed a comprehensive search for such factors and found LDL size to be weakly correlated with endothelium-dependent vasodilatation. 34 A similar relation was also described by Watts et al 11 within a group of type 2 diabetic patients. In other studies, 8,12,13 no significant correlations between cardiovascular risk factors and endothelium-dependent vasodilatation have been identified.…”
Section: Vehkavaara Et Al Insulin Therapy and Endothelial Functionsupporting
confidence: 65%
See 2 more Smart Citations
“…We recently performed a comprehensive search for such factors and found LDL size to be weakly correlated with endothelium-dependent vasodilatation. 34 A similar relation was also described by Watts et al 11 within a group of type 2 diabetic patients. In other studies, 8,12,13 no significant correlations between cardiovascular risk factors and endothelium-dependent vasodilatation have been identified.…”
Section: Vehkavaara Et Al Insulin Therapy and Endothelial Functionsupporting
confidence: 65%
“…The reason for normal endothelial function in the study of Avogaro et al is unclear but could be due to the small number of subjects studied (6 normal subjects and 10 patients with type 2 diabetes). Regarding endothelium-independent but guanylate cyclase-dependent vasodilatation, endothelial function has been found to be either impaired 8,11,12 or normal. 9,13 Multiple causes could contribute to endothelial dysfunction in patients with type 2 diabetes compared with nondiabetic subjects matched for age, body weight, LDL cholesterol levels, and blood pressure, as in the present study (Table 1).…”
Section: Vehkavaara Et Al Insulin Therapy and Endothelial Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the mean difference between type 2 diabetes and normal controls is 0.50 and 0.44 V, respectively [36,37], this represents a clinically relevant reversal of the abnormalities described. In terms of SD improvement, these represent 0.8 and 0.74 SD, which are smaller than many changes previously described for exercise-induced changes of the macrocirculation, many of which are multiples of SDs [13,38,39]. A type 2 error is therefore unlikely to explain the lack of an effect of exercise on microvascular function.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast, some authors have reported attenuated responses to nitrovasodilators in diabetic patients Ž . Watts et al, 1996 . In human aortic endothelial cells, prolonged exposure to elevated concentrations of glucose increases eNOS gene, protein expression and NO release, thus indicating that both basal and stimulated production of NO are enhanced Ž in high glucose-treated cells Cosentino and Luscher, . 1998 .…”
Section: Discussionmentioning
confidence: 99%